Picochlorum celeri as a model system for robust outdoor algal growth in seawater - Anagha Krishnan (Nature Portfolio, 2021)
Abstract With fast growth rates, broad halotolerance and the ability to thrive at high temperatures, algae in the genus Picochlorum are emerging as promising biomass producers. Recently, we isolated a remarkably productive strain, Picochlorum celeri, that attains > 40 g m−2 day−1 productivities using simulated outdoor light. To test outdoor productivities, Picochlorum celeri was cultivated in 820 L raceway ponds at the Arizona Center for Algae Technology and Innovation. Picochlorum celeri demonstrated the highest outdoor biomass productivities reported to date at this testbed averaging ~ 31 g m−2 day−1 over four months with a monthly (August) high of ~ 36 g m−2 day−1. Several single day productivities were > 40 g m−2 day−1. Importantly for sustainability, Picochlorum celeri achieved these productivities in saline water ranging from seawater to 50 parts per thousand sea salts, without any biocides or pond crashes, for over 143 days. Lastly, we report robust genetic engineering tools for future strain improvements.